2017
DOI: 10.14710/nmjn.v7i1.15125
|View full text |Cite
|
Sign up to set email alerts
|

Motivation among Indonesian Nurses in Pursuing Continuing Professional Education and Its Relationship to Their Competencies

Abstract: Background: Nurses are required to maintain the standards of their practice through an informed range of Continuing Professional Education (CPE). However, there is a paucity of evidence exploring the relationship between motivation in pursuing CPE and competency among Indonesian nurses.Purpose: This descriptive correlational study describes the motivation among Indonesian nurses in pursuing CPE and its relationship to their competency outcome performance.Methods: Ninety-three staff nurses were chosen by conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Several studies have revealed that moral courage is associated with concepts pertaining to the evaluation of ethics under specific contexts, such as resilience, 7,8,9 burnout 10,11 and motivation. 12,13 In the end, moral courage is defined by nurses' commitment to assist patients, comfort them in their suffering, communicate openly and honestly with them and their families, and consistently uphold the highest ethical standards despite moral and ethical constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that moral courage is associated with concepts pertaining to the evaluation of ethics under specific contexts, such as resilience, 7,8,9 burnout 10,11 and motivation. 12,13 In the end, moral courage is defined by nurses' commitment to assist patients, comfort them in their suffering, communicate openly and honestly with them and their families, and consistently uphold the highest ethical standards despite moral and ethical constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the results of this study, it is believed that classroom debates offer the students a valuable opportunity to develop critical thinking and oral communication abilities, as well as other necessary skills to face today's healthcare system. Critical thinking is associated with nurse performance (Suangga & Tuppal, 2017). Previous research reported that problem-based learning was the strategy that is mostly used to promote critical thinking in an undergraduate nursing course (Carvalho et al, 2017) and encourage students as self-directed learners (Kong, Qin, Zhou, Moub, & Gao, 2014).…”
Section: Discussionmentioning
confidence: 99%